The family farm in a globalizing world: the role of crop science in alleviating poverty - Lipton, Michael (International Food Policy Research Institute, 2005)
The topic of family farms has been gaining prominence in the academic, policy, and donor communities in recent years. Small farms dominate the agricultural landscape in the developing world, providing the largest source of employment and income to the rural poor, yet smallholders remain highly susceptible to poverty and hunger. With the advance of globalization and greater integration of agricultural markets, the need for increases in agricultural productivity for family farms is particularly pressing. Raising productivity and output of small farmers would not only increase their incomes and food security, but also stimulate the rest of the economy and contribute to broad-based food security and poverty alleviation. In this paper, Michael Lipton builds an argument for greater focus on pro-smallholder crop science as a key solution to generate increases in productivity and income. Increasing the levels of investment into agricultural technology, improving water and land use and distribution, and creating positive incentives for developing-country farmers come to the forefront of the paper as critical steps that must be taken to ensure massive reduction in global poverty. Favorable demographic trends over the next few decades provide a window of opportunity for reforms and action that must not be squandered.